Catalytic oxidation and reaction kinetics of low concentration benzene over CuxMnyOz/SiO2. (15th February 2021) - Fang, Ruiming; Yang, Zhongqing; Liu, Xianwei; Yan, Yunfei; Ran, Jingyu; Zhang, Li
Abstract: Reducing reaction temperature of catalytic combustion is the fundamental way to improve adaptability of catalysts to complex volatile organic compounds (VOCs) and off-design conditions. Using benzene which is the most difficult to be oxidized in VOCs as the catalytic target and by means of multiple characterization methods, silicon dioxide supported copper-manganese catalysts were optimized through changing the load of active material, the ratio of bimetal and calcination condition, the conclusions as following: Cu3 Mn9 /SiO2 with calcination temperature of 300 °C, molar ratio for Cu/Mn of 3:9 and total load mass for active substance of 11% demonstrates the best catalytic performance. And the benzene which is lower than 2000 mg/m 3 in air can be completely oxidized at 265 °C. The change of activation energy and mechanism of deactivation in the process of catalyst optimization were obtained by catalytic reaction kinetic analysis. After the optimization, reaction activation energy decreased from 65.08 kJ/mol to 56.82 kJ/mol, and complete conversion temperature of the C6 H6 decreased by nearly 20 °C. Additionally, the fundamental reason for deactivation of the catalyst is the structure changes at high temperature, and surface oxides agglomerate, which greatly reduces the oxygen content of the catalyst. With the increase of reaction temperature, the mass transfer capacity of O2 on the surface of catalyst increase less than that of C6 H6, leading to carbon deposition, and the joint action results in the decrease of catalyst activity.